TATA KELOLA PERUSAHAAN, PERTANGGUNGJAWABAN LINGKUNGAN, DAN NILAI PERUSAHAAN STUDI KASUS DI SEKTOR MANUFAKTUR DAN PERTAMBANGAN INDONESIA - Ainy, Rintan Nuzul (Optimum: Jurnal Ekonomi dan Pembangunan, 2016)
This study examines the relationship of corporate governance, environmentalresponsibility, and fi rm value in Indonesia. This study extends the literature by considers the role of environmental responsibility in the indirect relationship of corporate governance and fi rm value. The environmental responsibility data index is calculated by doing a content analysis of companyâs annual and sustainability report of 2013. The other data is obtained from OSIRIS database and Bursa Efek Indonesia.The result shows that voluntary activities such environmental responsibilityeffects the fi rm value. This study shows that there is no indirect relationship between corporate governance, environmental responsibility, and fi rm value in Indonesia.